TEACHING ACCOUNTING TO NON-TECHNICAL STUDENTS. - May, George O. (The Accounting Review, 1945)
Two considerations led the author to accept the invitation to prepare a paper on education for nontechnical students. The first was the great importance of the subject. The second consideration was a conviction that the opportunity and the responsibility must be shared by those who teach and those who practice accounting. A part of the task is to consider our responsibility for providing education that will result in the production of the best financial statements that can be devised. Another part is to promote recognition of the fact that the significance of such statements is both very great and definitely limited. Education upon this latter point is needed not only by businessmen and investors, but also by lawyers, economists, administrators, in fact, by all who occupy responsible positions in the national economic life. Failure to recognize the importance of the part played by accounting in the complex affairs of today is scarcely more common than a disposition to attach to accounts' significances which they cannot possibly possess.